Behind the screens Hollywood goes hypercommercial - Soar, Matt; Ericsson, Susan; Media Education Foundation ([Northampton, Mass.] : Media Education Foundation, 2000)
Discusses the idea that mainstream, big-budget movies have become largely a vehicle for advertising and marketing
Title from title screen
Executive producer, Sut Jhally ; editor, Susan Ericsson ; graphics, Matt Soar, Sut Jhally, Susan Ericsson ; music, Thom Monahan ; camera, Susan Ericsson...[et al.]
Keywords: Motion pictures -- United States -- History; Advertising -- Motion pictures -- United States; Documentary films -- United States